Suesses Gift - Heller, Peter (Germany, 2012)
Since the beginning of African states' independence from the colonial powers, developed countries have been dumping funds on the Black Continent. During the last 50 years, up to two trillion dollars have been transferred from other countries to Africa. Focusing on examples from Mali, Kenya and Tanzania, the film demonstrates that development aid has no positive effect. It is not a solution. Is it possibly the actual problem?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films